1993
DOI: 10.1210/endo.133.5.7691586
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 beta (IL-1 beta) modulates prostaglandin production and the natural IL-1 receptor antagonist inhibits ovulation in the optimally stimulated rat ovarian perfusion model.

Abstract: The rat ovarian perfusion model with bursa removed and intact was used to further characterize the effects of interleukin-1 beta (IL-1 beta) and the natural IL-1 receptor anatagonist (IRAP) on ovulation, steroidogenesis, and prostaglandin production. Twenty-six- to 27-day-old female Sprague-Dawley rats were injected sc with 25 IU PMSG, and 48 h later, the right ovary was dissected (with bursa removed and intact for various experiments) and placed in the perfusion chamber. Ovaries were exposed to various doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Similar results were reported by various workers in mammalian preovulatory follicles (Simon et al, 1994, Jasper et al, 1996Keck et al, 1998;Salmassi et al, 2001;Gerard et al, 2004). The expression of IL-1β, IL-6 and GM-CSF are related to several ovulation-associated events such as synthesis of plasminogen activator (PA) (Hamilton et al, 1993;Fujisaki et al, 2006;Kralisch et al, 2006), prostaglandin (Peterson et al, 1993;Neuvians et al, 2004) and nitric oxide (Yamauchi et al, 1997;Machelon and Emilie, 1997;Estevez et al, 2004) in mammals. In chicken, the PA activity in granulosa and theca cells (Jackson et al, 1993;Tischkau et al, 1996), prostaglandin F levels (Saito et al, 1987) and nitric oxide levels (Manwar et al, 2006;Sundaresan et al, 2007b) were higher in F1 follicles.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results were reported by various workers in mammalian preovulatory follicles (Simon et al, 1994, Jasper et al, 1996Keck et al, 1998;Salmassi et al, 2001;Gerard et al, 2004). The expression of IL-1β, IL-6 and GM-CSF are related to several ovulation-associated events such as synthesis of plasminogen activator (PA) (Hamilton et al, 1993;Fujisaki et al, 2006;Kralisch et al, 2006), prostaglandin (Peterson et al, 1993;Neuvians et al, 2004) and nitric oxide (Yamauchi et al, 1997;Machelon and Emilie, 1997;Estevez et al, 2004) in mammals. In chicken, the PA activity in granulosa and theca cells (Jackson et al, 1993;Tischkau et al, 1996), prostaglandin F levels (Saito et al, 1987) and nitric oxide levels (Manwar et al, 2006;Sundaresan et al, 2007b) were higher in F1 follicles.…”
Section: Resultssupporting
confidence: 79%
“…Cytokines are potent autocrine regulators of granulosa or thecal cell functions (Machelon and Emilie, 1997) and are involved in the temporal and spatial remodeling of granulosa and theca cells. Further, the autocrine production of the proinflammatory cytokines was found to influence ovarian steroidogenesis (Neuvians et al, 2004;Skarzynski et al, 2005), synthesis of plasminogen activator (Hamilton et al, 1993;Fujisaki et al, 2006;Kralisch et al, 2006), synthesis of prostaglandins (Peterson et al, 1993;Neuvians et al, 2004) and synthesis of nitric oxide (Yamauchi et al, 1997;Machelon and Emilie, 1997;Estevez et al, 2004). However, the spatial expressions of cytokines in avian follicles are not studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, we observed that intrafollicular injection of IL-1RA did not induce the ovulation process as observed with IL-1␤. IL-1RA, rather, would delay it, as 75% of the ovulations were observed more than 55 h after treatment and no ovulation was observed before 47 h. A retarding effect of IL-1RA on the ovulation process was already suggested by the results of Peterson et al [55], who used the rat ovarian perfusion model and demonstrated that IL-1RA induced a lower ovulation rate than LH during a period of 20 h of perfusion. Moreover, it has been shown that intrafollicular injection of indomethacin, another anti-inflammatory molecule, disturbs the normal follicle development [40,56].…”
Section: Discussionmentioning
confidence: 91%
“…It involved in several ovulation associated events such as synthesis of proteases, regulation nitric oxide and prostaglandin production [22]. On the other hand, previous studies has also found that hCG-induced ovulation rates were decreased in rats after treatment with IL-1 receptor antagonist (IL-1Ra) [23, 24]. Although IL-1α and IL-1β are encoded by different genes, they exert similar biological effects by binding to the same receptor (IL-1R1).…”
Section: Introductionmentioning
confidence: 99%